Visually Plastic Art Therapy in Reducing Anxiety of Chronic Low Back Pain Patients - Jurčenko, Aloida (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the research is to check if Art therapy reduces anxiety and pain symptoms for chronic low back pain patients. The selection of the research members was made by using structured interview. For the selection of anxiety research – C.D. Spielberg anxiety position-feature self-assessment (STAI from Y-1). For the selection of pain symptom detection was used numerical analog (ranking) scale (NRS). There were patients from 30 to 60 years old, who made the selection, all with M47.2 diagnosis and anxiety pain symptoms. The capacity of the selection in the end of the research was 54 patients (26 in the research group and 28 in the control group). Research group took part in art therapy (8 sessions). There were used descriptive and conclusive statistics for data analysis. There are several conclusion verdicts. Art therapy reduces anxiety and pain symptoms in chronic low back pain patients.